Measuring health care quality in public hospitals / Ahmad Zamie Azis...[et al.] - Azis, Ahmad Zamie; Kasmunee, Mohd Farhan; Ahmad, Jasmine (2010)
As competition intensified in the health care market, health care institutions has no choice but try to improve their efficiency and competitive advantages by improving their cost-effectiveness and quality of care. Patient-based determinants of quality and satisfaction play an important role in choosing a health care provider. This study identifies attributes of health care delivery that define patients' perceptions of quality and satisfaction. This study looks into the service quality dimensions as postulated in the SERVQUAL model, focusing on the difference between customers' expectation and perception of service delivered. Postal survey was implemented to sample of patients and visitors who underwent inpatient care to evaluate their overall experience of the service care. The samples of the study are patients from two public hospitals namely. Findings from the survey could contribute to the understanding of customer's expectation of the health care industry.